2018
DOI: 10.1088/1757-899x/390/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Process Parameter Optimization in TIG Welding of AISI 4340 Low Alloy Steel Welds by Genetic Algorithm

Abstract: Weld quality is an essential requirement to the fabrication and construction industries. In this present investigation, an attempt has been made to optimize the process parameters of Tungsten Inert Gas (TIG) welding of AISI 4340 low alloy steel. Taguchi L9 orthogonal array is used to design the experiment and response surface methodology was used to develop mathematical model and the process parameters were optimized using Genetic Algorithm (GA). The important process parameters namely welding current, voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It was observed that current and voltage had maximum effect on tensile strength in A-TIG welded joint. Vijay et al [23] optimized various process parameters in TIG weld on 4340 AISI steel. Taguchi L9 orthogonal array for experimental design and RSM technique was used for mathematical model and optimization of various parameters was done by using genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that current and voltage had maximum effect on tensile strength in A-TIG welded joint. Vijay et al [23] optimized various process parameters in TIG weld on 4340 AISI steel. Taguchi L9 orthogonal array for experimental design and RSM technique was used for mathematical model and optimization of various parameters was done by using genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…TIG welding can weld a variety of materials with varying degrees of success by using a V or U notch to boost the specimen's hardness. In order to optimise a process parameter, several studies employed Taguchi and ANOVA techniques [4][5][6][7]. TIG welding was used to examine the specimens' hardness and microstructure in this work.…”
Section: Introductionmentioning
confidence: 99%